A Study On The Techniques For Teaching Speaking To The Second Year Students Of SMP N 1 Trangkil - Rusdiningsih, Lia (2012)
The objectives of this study are to describe (1) techniques implemented by the teacher in teaching speaking, (2) problems faced by the students in teaching speaking and (3) Methods/techniques to overcome the problem faced by the students.To obtain the reserch data the writer conducted the observation in SMP N 1 Trangkil. The writer took the students in class VIII E as the sample. The writer also interviewed to the students and the teacher. The writer found that the techniques used by the teacher in teaching speaking are question-answer, role-play, and game techniques. The problems faced by the student are (1) the difficulty of pronunciation, (2) nervousness and shyness. Methods to overcome the problem faced by the students are: (1)asking the students to repeat after the teacher pronounced some words so they can know the correct of pronunciation, (2)asking the students to read a dialogue so the teacher can correct the pronunciation, (3)using a role-play technique in teaching speaking so the students can explore their capability, (4)making the students to get used to speak with her/his friends in front of the class so they were not afraid to speak, (5) to overcome shy and nervous students, the teacher used a game in teaching speaking